Earthworm Abundance and Soil Characteristics Following Cocoa Waste and Manure Applications - Erwin Prastowo; Lina Dwi Agustina; Cahyo Prayogo (Indonesian Coffee and Cocoa Research Institute, 2020)
Soil fertility level improvement in an environmentally friendlier way has been a key to provide a sustainable cocoa production. Earthworms, as decomposeragents in soil, may provide a sustainable way of improving soil fertility level. The objective of this study was to quantify top soil earthworm population andsome important soil characteristics, e.g. soil moisture, organic C, total N, and pH to see if there was any response observed due to different level and type oforganic waste applications. Their surface populations, i.e. at 5–10 cm depth, within cocoa circle were investigated with respect to different type of organic wasteapplications, i.e. cocoa pod waste, cocoa leaf waste, and sheep manure. For cocoa derived organic matter, the level of application was arranged at 5, 10, and 20 ton/ha to obtain an optimal condition at which the highest population of earthworm is obtained. A field investigation was performed at a square of 900 cm2 sizedarea, and extending down to 5–10 cm depth. Additionally, the effect of organic waste to top soil characteristics were also determined mainly to some importantparameters such as soil moisture, organic carbon, total nitrogen, and soil pH (H2O). Our analysis suggest that field heterogeneity condition may limit the conclusion, mainly related to the question of to what extent the effect of organic wastes to the changes in terms of soil characteristics. The application of organic wastes was able to increase the population of earthworms. Their highest abundance was obtained following the application of cocoa pod at 20 ton/ha, which was about 5 times higher than the population in the control.